Recycling Li-Ion Batteries via the Re-Synthesis Route: Improving the Process Sustainability by Using Lithium Iron Phosphate (LFP) Scraps as Reducing Agents in the Leaching Operation - Francesca Pagnanelli; Pietro Altimari; Marco Colasanti; Jacopo Coletta; Ludovica D’Annibale; Alyssa Mancini; Olga Russina; Pier Giorgio Schiavi (Metals)
The development of hydrometallurgical recycling processes for lithium-ion batteries is challenged by the heterogeneity of the electrode powders recovered from end-of-life batteries via physical methods. These electrode materials, known as black mass, vary in composition, containing differing amounts of nickel, manganese, and cobalt (NMC), as well as other chemicals, such as lithium iron phosphate (LFP). This study presents the results of the hydrometallurgical treatment of mixed NMC and LFP black masses aimed at creating flexible recycling processes. This approach leverages the reducing power of LFP to optimize the leach liquor composition for re-synthesizing NMC precursors. In particular, the leaching conditions were optimized based on the LFP content in the solid feed to maximize the extraction of key metals (Ni, Mn, Co, and Li). The leaching solid residue, graphite, was treated and characterized as a secondary raw material for new anode preparation. Iron phosphate was recovered by increasing the pH of the leach liquor, and the NMC precursors were obtained via coprecipitation. This process achieved a recycling rate of 51%, based on the black mass input and the mass of recovered elements in the output products. Additionally, substituting LFP scraps as the reducing agent in place of H2O2 reduced the recycling process’s environmental impact by avoiding 1.7 tons of CO2-equivalent emissions per ton of NMC black mass.